Socioeconomic crisis and aggressive behaviour of Greek adolescents. (September 2017) - Lazaratou, Helen; Kalogerakis, Zacharias; Economou, Marina; Xenitidis, Kiriakos
Background: Aggressive behaviours are common during adolescence. In Greece, adolescents and their families experience a severe and enduring recession with potentially adverse impact on mental health. Aim: This study aimed to examine the correlation between adolescents' aggressive behaviour and economic factors. Methods: The Buss–Perry Aggression Questionnaire (AQ) was used to measure aggression. Reduction in pocket money and three items of the Household Food Insecurity Access Scale were used to measure material deprivation as a result of the economic crisis. The questionnaires were administrated to a sample of 2, 159 adolescent students of the Greater Athens Metropolitan Area. Results: Students who during the previous 4 weeks had experienced household food insecurity (anxiety/uncertainty about food, insufficient food quality or insufficient food intake) or had their pocket money decreased within the last 6 months scored on average significantly higher in the AQ compared to their counterparts who did not. Conclusion: The shortage in basic goods due to the actual Greek economic crisis seems to be related to aggressive behaviours during adolescence and we should take this into account in clinical practice.